PENERAPAN MULTIMEDIA DALAM PEMBELAJARAN YANG EFEKTIF - Nugroho Adi Suryandaru (Jurnal Pendidikan dan Pengajaran Guru Sekolah Dasar (JPPGuseda), 2020)
APPLICATION OF MULTIMEDIA IN EFFECTIVE LEARNINGThe purpose of this study is to analyze the use of multimedia in learning. The research method is meta-analysis. The research begins by formulating the problem, then proceed by collecting existing research data through Google Scholar search. From the research obtained in the form of 7 relevant scientific journals. Research results from researchers were analyzed by quantitative comparison methods. Based on the results of the analysis, the use of multimedia in learning can improve student learning outcomes from the lowest 0.1% to the highest 1.2%..